Keamanan dan Jaminan Lingkungan Kerja Guru: Konsep Perlindungan Hukum Sistem Pendidikan Nasional - Yudi Yasmin Wijaya; Ali Mannagalli; Mujiburrohman Mujiburrohman; Yustus One Simus Parlindungan (Jurnal Interpretasi Hukum, 2026)
The upheaval of educational rights has become a disruptive trend in Indonesia. The physical and verbal abuse coming from parents or students become usual things, and these abnormalities have since created imbalance of rights and responsibility on the climate of education in Indonesia. The Act No. 23 of 2003 about National Education System, Act No. 14 of 2005 about Teachers, and Government Regulation No. 74 of 2008 about Teachers which do not give effective legal prescription, creates the legal ambiguity towards fulfilment of rights for Indonesian teachers. The rights to safe and healthy work environment concept within education law may become the stepping stone towards ensuring save and effective working environment on educational set and protects the future generation of pupils. This paper will examine through the proper concept of legal protection as the obligation of a nations towards its statutes in Act or Government Regulation of Indonesia. Through this normative research, the study will also focused towards the analysis of concept of rights to safe and healthy work environment of teachers as a whole.